2019
DOI: 10.1111/jocd.12913
|View full text |Cite
|
Sign up to set email alerts
|

The dermoscopic features of facial aging among Egyptians: A comparative study between males and females

Abstract: Summary Background Few studies have evaluated facial photoaging by dermoscopy. Only one study has been performed among Egyptians. Objective To study and compare the dermoscopic features of facial aging in males and females and to relate these features to clinical criteria. Methods This study included 217 subjects divided into two groups; 117 males and 100 females. Each group was classified into three subgroups according to age. The dermoscopic features were reported according to dermoscopy photoaging scale (DP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 10 publications
1
18
0
2
Order By: Relevance
“…A similar result was found in a study by El-Sayed et al, which reported that lentigo, superficial wrinkles, and hypo-hyperpigmented macules were also the three most common DPAS findings. 15 This result is in accordance with references stating that most people with skin of color (Fitzpatrick skin type III and IV) living in coastal area tend to have earlier and more rapid pigmentation changes (dyschromia) since the most common forms of photoaging in skin of color are lentigo and mottled pigmentation. 18 , 19 …”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…A similar result was found in a study by El-Sayed et al, which reported that lentigo, superficial wrinkles, and hypo-hyperpigmented macules were also the three most common DPAS findings. 15 This result is in accordance with references stating that most people with skin of color (Fitzpatrick skin type III and IV) living in coastal area tend to have earlier and more rapid pigmentation changes (dyschromia) since the most common forms of photoaging in skin of color are lentigo and mottled pigmentation. 18 , 19 …”
Section: Discussionsupporting
confidence: 90%
“…A study by El-Sayed et al in Egypt reported that a higher mean DPAS score was found in people aged older than 60 years compared to those under 60 years. 15 This is supported by Isik et al that reported significant changes in photoaging based on DPAS score at the fifth decade of life. 5 …”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations